Major urinary protein (MUP) profiles show dynamic changes rather than individual “barcode” signatures - Thoß, Michaela; Luzynski, Kenneth; Ante, Michael; Miller, Ingrid; Penn, Dustin J. (Frontiers in Ecology and Evolution, 2015)
House mice (Mus musculus) produce a variable number of major urinary proteins (MUPs), and studies suggest that each individual produces a unique MUP profile that provides a distinctive odor signature controlling individual and kin recognition. This ‘barcode hypothesis’ requires that MUP urinary profiles show high individual variability within populations and also high individual consistency over time, but tests of these assumptions are lacking. We analyzed urinary MUP profiles of 66 wild-caught house mice from eight populations using isoelectric focusing. We found that MUP profiles of wild male house mice are not individually unique, and though they were highly variable, closer inspection revealed that the variation strongly depended on MUP band type. The prominent (‘major) bands were surprisingly homogenous (and hence most MUPs are not polymorphic), but we also found inconspicuous (‘minor’) bands that were highly variable and therefore potential candidates for individual fingerprints. We also examined changes in urinary MUP profiles of 58 males over time (from 6 to 24 weeks of age), and found that individual MUP profiles and MUP concentration were surprisingly dynamic, and showed significant changes after puberty and during adulthood. Contrary to what we expected, however, the minor bands were the most variable over time, thus no good candidates for individual fingerprints. Although MUP profiles do not provide individual fingerprints, we found that MUP profiles were more similar among siblings than non-kin despite considerable fluctuation. Our findings show that MUP profiles are not highly stable over time, they do not show strong individual clustering, and thus challenge the barcode hypothesis. Within-individual dynamics of MUP profiles indicate a different function of MUPs in individual recognition than previously assumed and advocate an alternative hypothesis (‘dynamic changes’ hypothesis).